The Effect Of Determinant Factors In The Family On The Arrival Time Of Patients Stroke In Emergency Installation - Muhammad Ikhwan Kosasih; Nugrahaeni Firdausi; Erwin Yektiningsih; Zauhani Kusnul (Universitas STRADA Indonesia, 2020)
Stroke is an important health problem. The speed with which a stroke sufferer gets the right treatment cause a big influence on stroke management. This study analyze the influence of various factors in the family on the arrival time of stroke patients in the emergency department of the Kediri district hospital. The study was conducted during May-July 2019 and found stroke patients as many as 88. The result show that educational factors have a significant relationship with the level of knowledge, and the family age, job, people who knew the stroke and decision-makers in the family have a significant relationship with the time interval between the stroke attack with the arrival of patients in the emergency room. From this study, it can be concluded that family factors play an important role in the time interval between a stroke and the arrival of a patient on IGD to get proper treatment.